Peran Teknologi Finansial FinTech dalam Mengubah Layanan Perbankan Tradisional - Putri, Devindya Citra Prameisti; Lutfianti, Alya (Media Hukum Indonesia (MHI), 2024)
Advances in financial technology (FinTech) have had a significant impact on traditional banking services. FinTech offers faster, easier and more efficient financial solutions through innovations such as digital payments, peer-to-peer (P2P) lending and automated investment management, expanding access to financial services. In addition, FinTech contributes to financial inclusion by reaching communities that have not been served by conventional banks. However, banking is faced with challenges in terms of regulation, data security and competition. This research explores the impact of FinTech on the banking sector and the challenges that arise in the era of digitalization.